Actionable intelligence : a guide to delivering business results with big data fast! - Carter, Keith B., 1973- (Hoboken, New Jersey : Wiley, 2014)
Building an analysis ecosystem for a smarter approach to intelligence Keith Carter''s Actionable Intelligence: A Guide to Delivering Business Results with Big Data Fast! is the comprehensive guide to achieving the dream that business intelligence practitioners have been chasing since the concept itself came into being. Written by an IT visionary with extensive global supply chain experience and insight, this book describes what happens when team members have accurate, reliable, usable, and timely information at their fingertips. With a focus on leveraging big data, the book provides expert guidance on developing an analytical ecosystem to effectively manage, use the internal and external information to deliver business results.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Decision making; Strategic planning; Big data; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Big data; Decision making; Strategic planning; Electronic books; Electronic books